ORGANIZATION AND ACTIVITY OF STATE ARCHIVES IN ZARAFSHAN OASIS - Eshonov Mirvokhid (Western European Studies, 2024)
Under the conditions of independence, the state body managing the archive work is the "Ozarkhiv" agency under the Cabinet of Ministers of Uzbekistan. Its system includes territorial administrations of the Republic of Karakalpakstan, regions and the city of Tashkent, state archives under their care (their branches), and central state archives. Currently, there are more than 100 state archives in the Republic of Uzbekistan, which contain 8 million. more documents than collections are being preserved. These documents are widely used by historians, researchers, students and other specialists in scientific, cultural and educational work. This article describes the history of the state archive in Samarkand region
Keywords: Turkestan; Archive work; Council of People's Commissars